2007
DOI: 10.1055/s-2007-983777
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Strategy for the Synthesis of Aryl Ethers

Abstract: An efficient strategy for the construction of aryl ethers using aryl fluorides and silyl ethers is described. This protocol uses a sub-stoichiometric amount of silicon-based reagent and proceeds under milder conditions than previously reported reactions of this type.The aryl ether moiety is found in a wide range of bioactive molecules 1,2 and materials. 3 Not surprisingly, efforts toward developing efficient and convenient protocols for the synthesis of aryl ethers has received considerable attention. 4 The U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…As a result, the activation energy for C–F activation decreased as the number of fluorine increased. The similar phenomena was observed by Crespo and Martinez, Love, , and Sandford . No C–F bond activation was observed for the reaction of monofluorophenyl oxazoline as substrate (Table , entry 14).…”
Section: Resultssupporting
confidence: 82%
“…As a result, the activation energy for C–F activation decreased as the number of fluorine increased. The similar phenomena was observed by Crespo and Martinez, Love, , and Sandford . No C–F bond activation was observed for the reaction of monofluorophenyl oxazoline as substrate (Table , entry 14).…”
Section: Resultssupporting
confidence: 82%
“…No C–F bond activation was observed for the reaction of 2-(2-fluorophenyl)pyridine as substrate. Several groups have reported that the activation of the C–F bond in less fluorinated arenes were much more difficult than those in pentafluorophenyl substrates. ,, Jones and co-workers reported that the strength of the metal–Ar F bond increases with the increasing of the electronegativity of the aryl group . Consequently, the energy for C–F activation decreased as the number of fluorine increased.…”
mentioning
confidence: 99%